Mesoporous Pt electrocatalyst for methanol tolerant cathodes of DMFC - Franceschini, Esteban Andrés (2012)
High activity mesoporous Pt electrocatalyst, having 2D-hexagonal mesostructure, was synthesized using a triblock poly(ethylene oxide)-b?poly(propylene oxide)-b?poly(ethylene oxide) copolymer (Pluronic F127®) template. The catalyst was characterized for the oxygen reduction reaction (ORR) in a rotating ring disk electrode (RRDE) configuration, obtaining a high efficiency of conversion to H2O. The formation of H2O2 during the ORR was low and a change in Tafel slope analysis indicated a change in the reaction mechanism with temperature. It was found, through differential electrochemical mass spectrometry (DEMS) analysis, that the mesoporous Pt catalysts exhibit a high methanol to CO2 conversion efficiency and high tolerance to CO poisoning. The procedure described in this work for preparing mesoporous Pt catalyst by electrodeposition provides a simple method for the generation of high-performance cathodes for direct methanol PEM fuel cells.